EFEKTIVITAS SURAT SEBAGAI MEDIA KOMUNIKASI FORMAL DI LINGKUNGAN PENDIDIKAN - Rika Ramadhani Az Zahra; Tia Monika; Sundawati Tisnasari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Official letters are still widely used as a medium of formal communication in various educational settings, ranging from schools and education offices to higher education institutions. However, in practice, the effectiveness of letters as a means of conveying information and policies often encounters various linguistic constraints. This study aims to describe the effectiveness of letters as a formal communication medium in educational environments and to examine their relationship with writing skills. The study employs a qualitative approach with a descriptive qualitative research design. Data were obtained through in-depth interviews with school principals, teachers, educational staff, officials and staff of education offices, lecturers, higher education administrative staff, as well as eighth-grade junior high school students as supporting informants. The data were analyzed thematically through the stages of data reduction, data display, and conclusion drawing. The findings indicate that letters continue to play an important role as a formal communication medium, yet their effectiveness has not been fully optimized. The main problems identified include unclear language use, the employment of lengthy and overly normative sentences, and variations in writing quality influenced by the writers’ writing skills. The ineffectiveness of letters results in low levels of recipient comprehension and the emergence of a need for further clarification. This study concludes that the effectiveness of letters as a formal communication medium is highly dependent on the quality of formal writing skills. These findings imply the importance of strengthening official letter writing skills in school learning as well as in institutional communication practices within the education sector.